2013
DOI: 10.11138/jts/2013.1.4.1455
|View full text |Cite
|
Sign up to set email alerts
|

Rotational alignment of the tibial component in total knee arthroplasty: the anterior tibial cortex is a reliable landmark

Abstract: Purpose: to compare the anterior tibial surface curvature, the Akagi's line and the medial third of the tibial tubercle in order to assess which is the most reliable landmark for correct tibial component rotational positioning in total knee arthroplasty. Methods: three independent investigators reviewed 124 knee MRI scans. The most suitable tibial baseplate tracing for the Nexgen Total Knee System (Zimmer, Warsaw, USA) was superimposed on the scan matching the anterior tibial cortex with the anterior aspect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 26 publications
1
44
0
Order By: Relevance
“…To determine the rotational alignment of the tibial component in TKA, several anatomical landmarks on the proximal tibia have been proposed [1727]. Many studies have shown that the tibial tuberosity is a reliable landmark [24, 3537].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine the rotational alignment of the tibial component in TKA, several anatomical landmarks on the proximal tibia have been proposed [1727]. Many studies have shown that the tibial tuberosity is a reliable landmark [24, 3537].…”
Section: Discussionmentioning
confidence: 99%
“…1e) [27]; and (5) the AP axis of the tibial prosthesis, using a tibial prosthesis template (LPS-Flex; Zimmer, Warsaw, IN, USA), along the ATCC (Fig. 1f) [17]. Internal rotation was shown as a negative value, while external rotation was shown as a positive value.
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cemented PS femoral components from each group were aligned rotationally according to the patient's surgical transepicondylar. The rotational alignment of all cemented symmetric tibial components was set matching the contour of the tibial anterior cortex, following author's previously published surgical technique [17]. All patellae were replaced using a “free hand technique” without cutting guides, and tracking of the patella was checked using the “no thumb technique” [18].…”
Section: Methodsmentioning
confidence: 99%